2014
DOI: 10.1111/medu.12316
|View full text |Cite
|
Sign up to set email alerts
|

Legitimate workplace roles and activities for early learners

Abstract: Pre-clerkship students are capable of legitimately participating in patient care experiences to an extent not usually available to them. The SRC represents one example of how early clinical experiences in the core curriculum might be transformed through the provision of patient care activities of narrow scope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 32 publications
4
81
0
1
Order By: Relevance
“…22 In addition, students in even the first year of medical school have demonstrated the ability to participate in and contribute to the clinical workplace when given the opportunity, clear roles, and adequate support. 23 In the clinical workplace, trust is a key element of the supervision of learners. Here, clinical supervisors make decisions to invite learner participation or provide learner responsibilities for patient care based on their trust of the individual learner.…”
Section: Generalizability and Applicability Of Epa Principlesmentioning
confidence: 99%
“…22 In addition, students in even the first year of medical school have demonstrated the ability to participate in and contribute to the clinical workplace when given the opportunity, clear roles, and adequate support. 23 In the clinical workplace, trust is a key element of the supervision of learners. Here, clinical supervisors make decisions to invite learner participation or provide learner responsibilities for patient care based on their trust of the individual learner.…”
Section: Generalizability and Applicability Of Epa Principlesmentioning
confidence: 99%
“…[7][8][9][10] Undergraduate medical educators are beginning to consider how trust can inform student assessment, particularly in settings that afford longitudinal contact between students and supervisors and meaningful student roles. 11,12 Nationally, the Association of American Medical Colleges (AAMC) has proposed EPAs for graduating students to ensure readiness for residency. 13 However, to our knowledge, a process for developing student-level EPAs that address institutional program objectives, student competencies, and larger mandates for CBME has not been articulated.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Preliminary studies have shown that medical students in longitudinal clerkships can play a meaningful role in clinical care through patient advocacy even in the early stages of training, a concept known as "value-added medical education." 4,8,[13][14][15] These early successes have led medical education experts to call for further study and expansion of the model. 5,6,8 Longitudinal clerkships have been implemented in a variety of settings, predominantly with third-year students.…”
mentioning
confidence: 97%